Supporting New Teachers. The Finnish and Israeli Mentoring Models [Wspieranie nowych nauczycieli. Fiński i izraelski model mentoringu]. - Nowakowska-Siuta , Renata (Studia Edukacyjne, 2023)
In this article, we will have a closer look at two models of teacher mentoring, which for many years have been successfully operating in two culturally different countries: Finland and Israel. Following the methodology of comparative research according to Raymond Boudon, I will identify and briefly characterise the main social mechanisms, which lie behind the particular approach to mentoring in the two analysed models: Self-Determination Theory and Work Motivation (Israel) and Peer Group Mentoring (Finland), including the axiological-rational prerequisites for their application.